Microorganisms in our world - Atlas, Ronald M. (Mosby, 1995)
Microorganisms and microbiology -- Cellular and molecular microbiology -- Microbial growth and its control -- Microorganisms and human diseases -- Infectious diseases -- Applied and environmental microbiology